The effect of solvent quality on pathway-dependent solution-state self-assembly of an amphiphilic diblock copolymer - Venkataraman, Shrinivas (2020)
The cholesterol-functionalized polycarbonate-based diblock copolymer, PEG113-b-P(MTC-Chol)30, forms pathway-dependent nanostructures via dialysis-based solvent exchange. The initial organic solvent that dissolves or disperses the polymer dictates a self-assembly pathway. Depending upon the initial solvent, nanostructures of disk-like micelles, exhibiting asymmetric growth and hierarchical features, are accessible from a single amphiphilic precursor. Dioxane and tetrahydrofuran (THF) molecularly dissolve the block copolymer, but THF yields disks, while dioxane yields stacked disks after dialysis against water. Dimethylformamide and methanol display dispersed disks and then form stacked disk structures after dialysis. The path-dependent morphology was correlated to solubility parameters, an understanding of which offers routes to tailor self-assemblies with limited sets of building blocks.